KnowledgeBoat Logo

Mathematics

A(-3, 1), B(4, 4) and C(1, -2) are the vertices of a triangle ABC. Find :

(i) the equation of median BD,

(ii) the equation of altitude AE.

Straight Line Eq

9 Likes

Answer

(i) D is the mid-point of AC [∵ BD is median]

By mid-point formula,

D=(x1+x22,y1+y22)D=(3+12,1+(2)2)D=(22,12)D=(1,12)\Rightarrow D = \Big(\dfrac{x1 + x2}{2}, \dfrac{y1 + y2}{2}\Big) \\[1em] \Rightarrow D = \Big(\dfrac{-3 + 1}{2}, \dfrac{1 + (-2)}{2}\Big) \\[1em] \Rightarrow D = \Big(\dfrac{-2}{2}, \dfrac{-1}{2}\Big) \\[1em] \Rightarrow D = \Big(-1, -\dfrac{1}{2}\Big)

By two-point formula,

Equation of line : yy1=y2y1x2x1(xx1)y - y1 = \dfrac{y2 - y1}{x2 - x1}(x - x1)

∴ Equation of line passing through (4, 4) and (1,12)\Big(-1, -\dfrac{1}{2}\Big).

y4=12414×(x4)y4=1825×(x4)y4=925×(x4)y4=910(x4)10(y4)=9(x4)10y40=9x369x10y36+40=09x10y+4=09x+4=10y.\Rightarrow y - 4 = \dfrac{-\dfrac{1}{2} - 4}{-1 - 4} \times (x - 4) \\[1em] \Rightarrow y - 4 = \dfrac{\dfrac{-1 - 8}{2}}{-5} \times (x - 4) \\[1em] \Rightarrow y - 4 = \dfrac{-\dfrac{9}{2}}{-5} \times (x - 4) \\[1em] \Rightarrow y - 4 = \dfrac{9}{10}(x - 4) \\[1em] \Rightarrow 10(y - 4) = 9(x - 4) \\[1em] \Rightarrow 10y - 40 = 9x - 36 \\[1em] \Rightarrow 9x - 10y - 36 + 40 = 0 \\[1em] \Rightarrow 9x - 10y + 4 = 0 \\[1em] \Rightarrow 9x + 4 = 10y.

Hence, equation of median BD is 10y = 9x + 4.

(ii) By formula,

Slope = y2y1x2x1\dfrac{y2 - y1}{x2- x1}

Slope of BC = 2414=63\dfrac{-2 - 4}{1 - 4} = \dfrac{-6}{-3} = 2.

We know that,

Product of slope of perpendicular lines = -1.

⇒ Slope of BC × Slope of AE = -1

⇒ 2 × Slope of AE = -1

⇒ Slope of AE = -12\dfrac{1}{2}.

By point slope form, equation of AE :

yy1=m(xx1)y1=12[x(3)]2(y1)=[x+3]2y2=x32y+x=3+2x+2y=1x+2y+1=0.\Rightarrow y - y1 = m(x - x1) \\[1em] \Rightarrow y - 1 = -\dfrac{1}{2}[x - (-3)] \\[1em] \Rightarrow 2(y - 1) = -[x + 3] \\[1em] \Rightarrow 2y - 2 = -x - 3 \\[1em] \Rightarrow 2y + x = -3 + 2 \\[1em] \Rightarrow x + 2y = -1 \\[1em] \Rightarrow x + 2y + 1 = 0.

Hence, equation of altitude AE is x + 2y + 1 = 0.

Answered By

3 Likes


Related Questions